Self care for nurses : small doses for wellness - May, Natalie; Cunningham, Tim, 1978-; Fontaine, Dorrie K. (Sigma Theta Tau International, 2023)
Self Care for Nurses will take you on a journey to explore proven self-care tactics, including over 30 wellness practices that tend to your mind; bite-sized exercises, giving you practical inspiration and food for thought in applying the latest in self-care research; helpful vignettes and guidance from nurses and wellness experts; and special challenges to help you claim the peace and balance you want in all aspects of your life.
Keywords: Nurses -- Job stress.; Nursing -- Psychological aspects.; Stress management.; Self-care, Health.; Burn out (Psychology) -- Prevention.; Nurses -- Psychology.; Self Care -- methods; Nurses -- psychology; Self Care; Soins infirmiers -- Aspect psychologique.; Gestion du stress.; Autothérapie.; Work-Related Health.; HEALTH & FITNESS.; MEDICAL.; Nursing.; Nurses -- Job stress; Nursing -- Psychological aspects; Self-care, Health; Stress management; Electronic books.